2021
DOI: 10.1101/2021.03.26.437236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Purkinje Cell Activity in Medial and Lateral Cerebellum During Suppression of Voluntary Eye Movements in Rhesus Macaques

Abstract: Conscious control of actions helps us to reach our goals by suppressing responses to distracting external stimuli. The cerebellum has been suggested to complement cerebral control of inhibition of targeted movements (conscious control), though by what means, remains unclear. By measuring Purkinje cell (PC) responses during antisaccades, we show that the cerebellum not only plays a role in the execution of eye movements, but also in during the volitional inhibition thereof. We found that simple spike (SS) modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(186 reference statements)
2
1
0
1
Order By: Relevance
“…This is because we did not find any correlation between the time of simple spike activity and the time of complex spike activity. These results are in line with the previous studies which showed a learning dependency on the activity of simple spike, independent of the complex spike in reward-based learning (Larry et al, 2019) and motor learning (Ke et al, 2009;Streng et al, 2018;Avila et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…This is because we did not find any correlation between the time of simple spike activity and the time of complex spike activity. These results are in line with the previous studies which showed a learning dependency on the activity of simple spike, independent of the complex spike in reward-based learning (Larry et al, 2019) and motor learning (Ke et al, 2009;Streng et al, 2018;Avila et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…This is because we did not find any correlation between the time of simple spike activity and the time of complex spike activity. These results are in line with the previous studies which showed a learning dependency on the activity of simple spike, independent of the complex spike in reward based learning (Larry et al, 2019) and motor learning (Avila et al, 2021;Ke et al, 2009;Streng et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…However, motor learning and optimization do not always entail CS activity providing a teaching signal for SS responses [8][9][10] . Furthermore, recent evidence suggest that cerebellar activity is correlated with aspects of behavior that do not involve correcting the kinematics of movement: for example classical conditioning 11 , stimulus prediction 12,13 , and the magnitude of predicted reward 14,15 .…”
mentioning
confidence: 99%